DIGITAL HUMAN RESOURCE MANAGEMENT AND INNOVATIVE WORK BEHAVIOR OF PONTIANAK CITY ASN IN IMPROVING THE QUALITY OF PUBLIC SERVICES: THE ROLE OF CHANGE READINESS AND TECHNOLOGY SUPPORT - Romawi Marthin; Nur Afifah; Mustaruddin; Titik Rosnani (RADJA PUBLIKA, 2026)
Digital transformation in the public sector encourages government organizations to develop Digital Human Resource Management (Digital HRM) practices that are not only oriented towards administrative efficiency but also towards the formation of innovative work behavior of ASN. This study aims to analyze the influence of Digital HRM on Innovative Work Behavior (IWB) of ASN and its implications for the quality of public services by considering the role of readiness to change and technological support in ASN Pontianak City Government. The study uses a quantitative approach with an explanatory research design. Data were collected through a survey of 200 ASN and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Digital HRM has a positive and significant effect on Innovative Work Behavior of ASN. Readiness to change is proven to mediate the relationship between Digital HRM and innovative behavior of ASN, while technological support has a direct effect on innovative behavior but is unable to strengthen the relationship between Digital HRM and Innovative Work Behavior in a moderating manner. This study also found that Innovative Work Behavior has the strongest influence on the quality of public services, while the direct effect of Digital HRM on the quality of public services is not significant. These findings indicate that the success of digital bureaucratic transformation is determined not only by technological systems, but also by the psychological readiness of civil servants (ASN) and the organization's ability to build a culture of public service innovation. This research provides a theoretical contribution by integrating technological and organizational behavior perspectives to explain digital HRM transformation in the public sector.